Dilution of precision for time difference of arrival with station deployment - Fengyun Zhang; Hao Li; Yulong Ding; Shuang‐Hua Yang; Li Yang (IET Signal Processing)
Abstract A study is conducted with the aim to reveal the relationship between the performance of moving object tracking algorithms and tracking anchor (station) deployment. The dilution of precision (DoP) for the time difference of arrival (TDoA) technique with respect to anchor deployment is studied. Linear and non‐linear estimators are used for TDoA algorithms. The research findings for the linear estimator indicate that the DoP attains a lower value when other anchors are scattered around a central anchor; for the non‐linear estimator, the DoP is optimal when the anchors are scattered around the target tag. Experiments on both algorithms are conducted that target location precision related to anchor deployment in practical situations for tracking moving objects integrated with a Kalman filter in an ultra‐wideband (UWB)‐based real‐time localization system. The work provides a guideline for deploying anchors in UWB‐based tracking systems.